Production optimization of a thermostable alkaline and detergent biocompatible protease by Bacillus paramycoides WSA for the green detergent industry - Wafa A. Alshehri; Sarah A. Alhothifi; Ashjan F. Khalel; Fatimah S. Alqahtani; Bilel Hadrich; Adel Sayari (Scientific Reports)
Abstract Industrial applications are evolving to replace chemical catalysts with eco-friendly solutions. This work enhances extracellular protease production from a newly isolated proteolytic Bacillus paramycoides WSA using Response Surface Methodology (RSM). The used quadratic model demonstrated a good fit with R2 = 80.59%, R2 Adj = 57.94%, a high degree of significance (p = 0.017 < 0.05), and a low RMSE = 0.030 U/mL. Maximum protease activity of 1.346 ± 0.060 U/mL was obtained after 8 h-cultivation at 45 °C and pH 7. The protease activity is maximal at 45 °C and pH 10. It maintains 75% of its activity after 10 min of incubation at 80 °C. Furthermore, the enzyme was found to be stable in an alkaline environment, retaining 89% of its activity after 1 h incubation at pH 12. Several metal ions, surfactants, and inhibitors increased protease performance. Indeed, 110% and 140% protease activity was measured in the presence of 5 mM CoCl2 and CaCl2, respectively. Similarly, 105%, 128%, 135%, 144%, and 160% protease activity were measured in the presence of 0.5% of Tween 20, EDTA, Sodium azide, uric acid, and SDS, respectively. Interestingly, the enzyme activity was enhanced (138%) after 1 h of incubation with 1% Reem detergent. Furthermore, this protease (10 U/mL), in combination with 0.7% detergent, could clean bloodstained fabric after 10 min incubation at 45 °C. Our results suggest that this thermostable, alkaline, and detergent-biocompatible protease could be a promising additive for eco-friendly use in detergent industries.